2012
DOI: 10.1177/0306624x12465583
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder in Offenders and the Need for Early Intervention

Abstract: Attention deficit hyperactivity disorder (ADHD) can be, for some people, a pathway to prison. Intervening at an early age may prevent delinquency. Generally, these interventions consist of a combination of medication, cognitive-behavioral therapy, family intervention, and educational support. Despite these interventions, some people with ADHD still develop antisocial and criminal behavior. This article examines the link between ADHD and delinquency, and reviews relevant treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…It has been suggested that this poor identification may be due to ineffective screening/assessment procedures during interviewing (Young et al, 2013), with staff knowledge, skill and training in the area failing to parallel the high rate of ADHD in the CJS (Young, Adamou et al, 2011). Researchers have suggested a need for such training to better accommodate these vulnerable interviewees and to facilitate early intervention (Belcher, 2014). The literature particularly stresses the important role of the juvenile CJS in the early identification and intervention-referral of youth with ADHD for a preventive approach (Collins & White, 2002;DeLisi et al, 2013;Einarsson et al, 2009;Gudjonsson & Young, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this poor identification may be due to ineffective screening/assessment procedures during interviewing (Young et al, 2013), with staff knowledge, skill and training in the area failing to parallel the high rate of ADHD in the CJS (Young, Adamou et al, 2011). Researchers have suggested a need for such training to better accommodate these vulnerable interviewees and to facilitate early intervention (Belcher, 2014). The literature particularly stresses the important role of the juvenile CJS in the early identification and intervention-referral of youth with ADHD for a preventive approach (Collins & White, 2002;DeLisi et al, 2013;Einarsson et al, 2009;Gudjonsson & Young, 2006).…”
Section: Discussionmentioning
confidence: 99%
“… 12 On the other hand, a significantly elevated risk for oppositional defiant disorder, conduct disorder, and many long-term adverse outcomes, including criminality, are frequently found in children with ADHD. 13 15 Barkley detected that children with ADHD were more likely to engage in a variety of antisocial activities in comparison with a control group, and that the frequency of such activities was largely predicted by the severity of ADHD in childhood and adolescence. 10 Prospective studies reported that children having high levels of ADHD often show disruptive behavior patterns, especially during adolescence, suggesting that hyperactivity could be a predictor of antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Problems in these areas may potentially threaten a young person's development. Hence, it is important that healthcare providers, especially those in youth-ACT settings, identify the causes underlying these problems, and subsequently initiate treatment interventions that are likely to meet the unmet care needs in question [48,[55][56][57][58]. For children and adolescents with ADHD belonging to a high-risk sample, such as those who are treated with youth-ACT, this implicates that routine assessment of school functioning, being one of the hallmarks of state-of-the-art investigation, may not be enough.…”
Section: Comparing Outpatient Clinics With Youth-actmentioning
confidence: 99%